Manajemen Persediaan dan Perencanaan Produksi Desain Interior pada CV. Elshaday Citra Sentosa - Michael Aninditya Hermawan; Yulia Yulia; Tanti Octavia (Jurnal Infra, 2019)
CV. Elshaday Citra Sentosa is a company engaged in furniture / interior design. Before starting the furniture production process, checking the supply of raw materials and carrying out production planning is a must. At this time, the company still uses simple records for management planning, raw material requirements planning, production scheduling and production supervision / supervision.Based on these problems, the author designed a program to solve the company's problems in controlling the production process. For the program making process, system analysis and design are needed. System analysis and design is done by using data flow diagrams (DFD) and entity relationship diagrams (ERD). Furthermore, this program was created using HTML, Bootstrap, PHP, AJAX, Javascript and MySQL as a database.The result of the development of this program is that the company can know the planning of raw materials and the duration of production only by entering the specifications of the products ordered by customers. Furthermore, the company can record the work stages of a product, raw materials used to produce the product, along with the workforce on duty. The results of testing to users and questionnaires indicate that the features and calculations in the program is close to the result of manual calculation so that they can answer the needs of the company in conducting inventory management, planning, supervision, and production control.